Roots of equity: women\'s roles and gender disparities in Brazil\'s ecological restoration - Siqueira, Ludmila Pugliese de (2024)
The present research titled \"Roots of Equity: Women\'s Roles and Gender Disparities in Brazil\'s Ecological Restoration\" explores gender disparities and the crucial role of women in ecological restoration in Brazil. Recognizing the importance of ecological restoration in addressing global biodiversity and climate change crises, it is argued that gender inclusion is essential for the success and sustainability of these initiatives. The research is structured into two main chapters. The first chapter, \"Gender Inclusion: Why Ecological Restoration Cannot Be Neutral\", lays the theoretical foundation for the discussion on the importance of gender equality in ecological restoration. It is asserted that restoration must be inclusive, considering human diversity, especially gender issues, as a critical factor for the success of projects. Moreover, the adoption of gender-responsive approaches in restoration practices is proposed, suggesting that gender equality should be viewed both as a driver and a measure of success. The second chapter, \"Gender Disparity and Biases in Ecological Restoration in Brazil,\" provides an empirical analysis of gender inequalities in the restoration sector in Brazil. The research covers various sectors, including scientific publications, participation in restoration supply chains, restoration coalitions, and gender perceptions among landowners involved in restoration projects. The results show that, although women\'s participation in scientific publications has increased, there is still significant underrepresentation of women in jobs and leadership positions in the restoration field. Additionally, a considerable number of women reported experiencing discrimination and harassment, especially in field activities. The conclusions of this research emphasize that, despite some progress, gender disparities remain a substantial challenge in ecological restoration in Brazil. It is proposed that the adoption of gender equity policies, the creation of safer and more inclusive work environments, and the encouragement of female participation through financial mechanisms such as Payments for Ecosystem Services (PES) are essential to promote equity and maximize the social and ecological benefits of restoration. This work contributes to the field of ecological restoration by highlighting the need to integrate gender considerations into restoration practices, ensuring that efforts to recover and regenerate ecosystems also pave the way for building a more inclusive and equitable society.